Systematic Quality Improvement on a Piston Machining Line Using DOE and Test for Variance - D. Sreenivas Rao3, Rajat Nayak1, Prashanth L2 (International Journal of Engineering Technology and Computer Research, 2015)
The globalization of industry and the competiveness has driven every manufacturing organizations to produce defect less and high quality product to satisfy the demands of the varying world market. Therefore quality is the key parameter which plays a vital role in manufacturing industries and products are tested for quality, regulated and certified. Some of the machining lines of Piston Machine Shop (PMS) of Federal Mogul Goetze (India) Limited were experiencing problems with quality and leading to losses of which machining line-02 (ML-02) which runs continuously through all the year with a significant output was identified which has maximum rejection rate accounting to 15.67% among all the machining lines which was considerably higher for its production volume and therefore it was identified for quality improvement. The tools like SPC, DOE and test for variance were used for improving the quality of the pistons in the ML-02. The result obtained after implementing Oil cooling system and new statistical way of rejection entry showed that the percentage rejection rate of skirt diameter reduced from 2.56% to 1.33% and hence the total percentage rejection on ML-02 was reduced from 17.26% to 9.56%. Keywords: Quality improvement, SPC tool, DOE, Variance test.